Treatments for stroke prevention in atrial fibrillation: A network meta-analysis and indirect comparisons versus dabigatran etexilate - Roskell, Neil S.; Lip, Gregory Y. H.; Noack, Herbert; Clemens, Andreas; Plumb, Jonathan M. (Thrombosis and Haemostasis, 2010)
Patients with atrial fibrillation at moderate to high risk of stroke are not always anticoagulated despite a lack of contraindications to vitamin K antagonists (VKAs) like warfarin. These patients are treated with aspirin, aspirin-clopidogrel combination therapy or even receive no thromboprophylaxis. The oral direct thrombin inhibitor, dabigatran etexilate 150 mg BID and 110 mg BID, might represent an alternative for these patients; however, no head-to-head clinical trial data exist versus these alternative treatments. A network meta-analysis (NMA) was performed to indirectly compare dabigatran etexilate with antiplatelets and placebo. Compared with placebo, dabigatran etexilate 150 mg BID was estimated to significantly reduce the risk of any stroke (ischaemic and haemorrhagic) by 75% (relative risk [RR] 0.25; 95% confidence interval [CI] 0.12–0.51), ischaemic stroke by 77% (RR 0.23; 95% CI 0.14–0.38), systemic embolism by 83% (RR 0.17; 95% CI 0.05–0.50) and mortality by 36% (RR 0.64; 95% CI 0.45–0.91). Dabigatran etexilate 150 mg BID was estimated to significantly reduce the risk of any stroke compared with aspirin monotherapy by 63% (RR 0.37; 95% CI 0.20–0.69) and aspirin plus clopidogrel by 61% (RR 0.39; 95% CI 0.21–0.72). Trends toward reduced risk with both dabigatran etexilate regimens were found for most clinical outcomes. Relative risk estimates of dabigatran etexilate versus adjusted-dose VKAs within the NMA were consistent with results from the head-to-head randomised trial of these two strategies. Indirect evidence suggests treatment with dabigatran etexilate offers benefit for the prevention of stroke, systemic embolism and mortality over antiplatelets and placebo. There was no indication of increased intracranial or extracranial haemorrhage with dabigatran etexilate compared to antiplatelet agents.
Keywords: Anticoagulation; atrial fibrillation; dabigatran; meta-analysis; stroke; thrombosis